The Merits of Sports Without Masses - Muazzez ŞAŞMAZ ATAÇOCUĞU (ümit doğan üstün, 2023)
The book under review is presented on its inner cover as a critique of the persisting misconceptions surrounding sports, which have endured since the inception of the Republican era and persist to the present time. The literary work entitled "Why Not Sports Without Masses" comprises a total of eleven distinct titles. The titles are as follows: "Introduction," "Orientation to Youth," "Clubs," "Athletes," "Training of Trainers," "Federations," "Management: A Job That Anyone Can Do," "Ministry," "Head Office," and "Foundationless Facility." Does Participation in Sports Contribute to Overall Health? The Significance of Sports for the General Population: An Analysis The author explores the topic of "Why Sport for the Mass?" in their work. The preceding sections have examined the errors in the execution, implementation, administration, and organization of sports, supported by illustrative instances and empirical evidence. Thus far, it has been comprehended that the comprehension of sports among the general population remains significantly distant given the prevailing circumstances. However, the crucial aspect pertains to determining the necessary actions and strategic considerations required to achieve this objective. The author underscores the importance of regarding the concept of "Sports for the Mass" with earnestness, rather than dismissing it as a mere popular discourse. The author contends that the interconnection between sports and societal issues necessitates a proactive approach, rather than a state of inaction.